Interconnection Between Citizenship Education and Law: Understanding the Role of Education in Shaping Community Legal Awareness - Purwantiningsih, Ary; Kusnadi (Universitas Negeri Semarang, 2024)
The interconnection between citizenship and legal education is a relevant phenomenon in the context of forming people's legal awareness. This article aims to understand the role of education in shaping people's legal awareness through analyzing the relationship between citizenship education and legal understanding. The qualitative analysis method of literature studies is used to explore the contribution of citizenship education in increasing legal understanding and awareness among the community. The research results highlight the importance of integrating legal concepts in the citizenship education curriculum to improve society's overall legal understanding. The implications of this interconnection show that citizenship education has an important role in forming better attitudes, values ​​and legal awareness in society. By strengthening the relationship between citizenship education and legal understanding, law-based community development efforts can be significantly enhanced.